2006
DOI: 10.1021/jp062579e
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer from Tetrasulfonated Porphyrin to Benzoquinone Revisited. The Structural Volume-Normalized Entropy Change Correlates with Marcus Reorganization Energy

Abstract: Time-resolved laser-induced optoacoustic spectroscopy was used for the determination of the enthalpy, DeltaTH, and structural volume changes, DeltaTV, concomitant with triplet state formation upon excitation of meso-tetrakis(4-sulfonatophenyl)porphyrin, TSPP(4-), as well as with the triplet state electron-transfer (ET) quenching by benzoquinone, BQ (DeltaRH and DeltaRV). The values of DeltaTH and DeltaTV for (3)TSPP(4-) formation in the presence of different cations (Li+, Na+, K+, NH4+, and Cs+) correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The energetic distance of the T 1 → S 0 transitions for this porphyrin is 1.43 eV [13]. It has been shown that the conduction band potential of the TiO 2 semiconductor is −0.5 V versus anatase (NHE), and the ground oxidation potential of TSPP porphyrin is 0.98 V in N,N -dimethylformamide [11]. Hence, from simple calculations it is possible to conclude that for TSPP coupled with TiO 2 both singlet and triplet states lie above the conduction band of TiO 2 , which suggests the electron transfer is energetically favorable from singlet and triplet states of TSPP involved in the complex, assuming that the singlet-triplet energy gap is the same as for TSPP (0.48 eV).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The energetic distance of the T 1 → S 0 transitions for this porphyrin is 1.43 eV [13]. It has been shown that the conduction band potential of the TiO 2 semiconductor is −0.5 V versus anatase (NHE), and the ground oxidation potential of TSPP porphyrin is 0.98 V in N,N -dimethylformamide [11]. Hence, from simple calculations it is possible to conclude that for TSPP coupled with TiO 2 both singlet and triplet states lie above the conduction band of TiO 2 , which suggests the electron transfer is energetically favorable from singlet and triplet states of TSPP involved in the complex, assuming that the singlet-triplet energy gap is the same as for TSPP (0.48 eV).…”
Section: Resultsmentioning
confidence: 95%
“…Using photoacoustic (PAS) spectroscopy [9], the heat produced by TiO 2 and TiO 2 -TSPP powdered samples were recorded. To record the time-resolved photothermal signals, the laser-induced optoacoustic spectroscopy (LIOAS) method [10,11] was applied. The excitation source was the nitrogen-dye laser (Photon Technology Int., GL-3300/GL301), and the detection system was operated using a piezoelectric transducer (Panametric Inc.,V1030).…”
Section: Measurementsmentioning
confidence: 99%
“…Pulsed time-resolved photoacoustics provides an unique way to probe the molecular mechanism of electron transfer and proton transfer events in chemical reactions (Braslavsky & Heibel, 1992;Chen & Dibold, 1996;Borsarelli & Braslavsky, 1999; Andres et al, 2006;Crovetto et al, 2006;Davies et al, 2008) and photosynthetic systems (Malkin, 2000;Herbert et al, 2001;Delosme, 2003;Mauzerall, 2006). For a given photoreaction, the accessible parameters include the molecular volume change secondary to conformational change or electrostriction, and enthalpy changes.…”
Section: Principle Of Pulsed Photoacousticsmentioning
confidence: 99%
“…Pulsed time-resolved photoacoustics provides an unique way to probe the molecular mechanism of electron transfer and proton transfer events in chemical reactions [17] and in biological systems, including photosynthetic complexes [816] and retinal-based pigments such as halorhodopsins [17,18], bacteriorhodopsins [1924] and rhodopsins [25,26]. For a given photoreaction, the accessible parameters include the molecular volume change secondary to conformational change or electrostriction, and enthalpy and entropy changes.…”
Section: Introductionmentioning
confidence: 99%